Analysis of Middle-size Enterprise Resource Planning Systems - Lehőcz, Gábor (Acta Agraria Kaposváriensis, 2008)
In the first part of this one of the most developing markets, the sales of the ERP (Enterprise Resource Planning) systems for middle-size companies in Germany were analyzed. The study was accomplished within a frame of a scholarship in the center of the German proALPHA Consulting AG in Hamburg, in March of 2007. SAP AG is salient from the ERP suppliers with a nearly 1,5 billion income in 2005. Considering the incomes from the systems made for middle-size companies and from the functionally associated consultant networks, the companies with 200-300 employees dominates this segment of the market. In the second part of the paper the various modules and functionalities of the ERP were investigated. This concludes in an ERP solution map, which contains also a suggestion to complete the functionalities of the German middlesize ERP called proALPHA. The optimization module of the ERP systems has been studied more detailed in the third part of the paper. A global and a local optimizing process were analyzed with the knowledge of the PPS (Production Planning System) module of the proALPHA. Based on the investigations the generic/genetic model based suboptimal solution generating algorithm (developed in our Department) seems to be applicable in the PPS module of proALPHA.